Uterine Prolapse in Postmenopausal Women in the Coastal Areas - Juminten Saimin; Indria Hafizah; Nina Indriyani; Ashaeryanto; Satrio Wicaksono (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: To assess the characteristics of postmenopausal women in the coastal areas that experience uterine prolapse. Methods: This was a retrospective descriptive study conducted at Alpha Gynecology Clinic in Kendari. Samples are cases of uterine prolapse from coastal areas that visited in January to December 2017. Samples were taken by consecutive sampling. The diagnosis of uterine prolapse is based on the Pelvic Organ Prolapse Quantification system. Data is presented with tables and narration. Results: There were 21 respondents who experienced uterine prolapse. Most respondents were aged 61-70 years (42.8%), work as housewives (71.4%), parity more than 4 (85.7%), and duration of menopause >5 years (100.0%). The most common complaint at the fi rst time was a feeling of a lump in the vagina (81.0%), in the third degree of uterine prolapse (57.1%), and accompanied by comorbidities (66.7%). Conclusions: Uterine prolapse in postmenopausal women in the coastal areas was found in housewives, aged 61-70 years, grande-multiparous, and duration of menopause >5 years. The main complaint was felt a lump in the vagina, in the third degree and accompanied by comorbidities. Counselling, information and education regarding symptoms and management of uterine prolapse need to be done. Keywords: coastal areas, postmenopausal women, uterine prolapse.